2022
DOI: 10.1371/journal.pone.0267884
|View full text |Cite
|
Sign up to set email alerts
|

Darunavir-cobicistat versus lopinavir-ritonavir in the treatment of COVID-19 infection (DOLCI): A multicenter observational study

Abstract: Background Coronavirus Disease 2019 (COVID-19) is an evolving pandemic that urged the need to investigate various antiviral therapies. This study was conducted to compare efficacy and safety outcomes of darunavir-cobicistat versus lopinavir-ritonavir in treating patients with COVID-19 pneumonia. Methods and findings This retrospective, multicenter, observational study was conducted on adult patients hospitalized in one of the COVID-19 facilities in Qatar. Patients were included if they received darunavir-cob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Additionally, a subgroup analysis of data from this study showed a lower risk of death in patients with mild disease treated with LPV/r [38]. Another observational study comparing the e cacy of early administered DRV/c versus LPV/r unravelled that LPV/r was associated with faster time to recovery and virological clearance, but not DRV/c [39]. These ndings can be also attributed to the unfavourable toxic side-effects of DRV/c [40].…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, a subgroup analysis of data from this study showed a lower risk of death in patients with mild disease treated with LPV/r [38]. Another observational study comparing the e cacy of early administered DRV/c versus LPV/r unravelled that LPV/r was associated with faster time to recovery and virological clearance, but not DRV/c [39]. These ndings can be also attributed to the unfavourable toxic side-effects of DRV/c [40].…”
Section: Discussionmentioning
confidence: 73%
“…A small randomized clinical trial in China involving mild COVID-19 patients treated with darunavir/cobicistat for five days on top of interferon-alpha 2b inhalation or interferon alpha 2b inhalation alone did not demonstrate any increase in the proportion of negative conversion compared to standard of care alone [ 123 ]. Also, an observational study in Qatar involving adult patients hospitalized for COVID-19 found that early treatment with lopinavir-ritonavir resulted in faster clinical improvement and/or virological clearance than darunavir/cobicistat [ 125 ]. Furthermore, a large cohort study of Italian patients hospitalized in 33 hospitals found that while the use of lopinavir/ritonavir did not change the death rate, the use of darunavir/cobicistat increased mortality [ 126 ].…”
Section: Antiviral Therapy Against Covid-19mentioning
confidence: 99%
“…An updated systematic review examined whether the use of LPV/r could be more favorable compared to the standard therapies regarding the length of stay, time for positive-to-negative conversion of SARS-CoV-2 and mortality in hospitalized patients with COVID-19, concluding that LPV/r had no significant advantage and also registered a significant increase in the occurrence of side effects [ 40 ]. However, Elmekaty et al [ 41 ] showed that early treatment with LPV/r is associated with a faster clinical improvement and/or virological clearance than the darunavir/cobicistat therapy in patients with COVID-19 pneumonia, and that the safety profile was quite comparable. Finally, Wong et al [ 42 ] discourage the use of LPV/r for pediatric COVID-19 cases because of their negative clinical outcomes, reporting a longer time for clinical improvement, seroconversion, hospital discharge, together with a higher risk of a hyperinflammation.…”
Section: Antiviral Drugsmentioning
confidence: 99%